2023
DOI: 10.1039/d3dt03233g
|View full text |Cite
|
Sign up to set email alerts
|

Design of polymetallic sulfide NiS2@Co4S3@FeS as bifunctional catalyst for high efficiency seawater splitting

Mingshuai Chen,
Guangping Wu,
Xiaoqiang Du
et al.

Abstract: This work describes the use of NiS2@Co4S3@FeS as a catalyst, which provides a current density of 10 mA cm−2 with a required potential of only 1.587 V, with an emphasis on its remarkable OER selectivity for seawater splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…31–34 However, the current densities of most catalysts were generally below 200 mA cm −2 , which is still not comparable to commercial noble metal catalysts and cannot meet the requirements of industrial water electrolysis. 35–37 In addition, the long-term stability is another bottleneck issue for practical electrolysers. The majority of the reported electrocatalysts usually work well only at small current densities (<100 mA cm −2 ) and dilute Cl − concentration (0.5 mmol L −1 ) for several hours (<50 h), which cannot meet the industrial requirements of practical electrolyzers.…”
Section: Introductionmentioning
confidence: 99%
“…31–34 However, the current densities of most catalysts were generally below 200 mA cm −2 , which is still not comparable to commercial noble metal catalysts and cannot meet the requirements of industrial water electrolysis. 35–37 In addition, the long-term stability is another bottleneck issue for practical electrolysers. The majority of the reported electrocatalysts usually work well only at small current densities (<100 mA cm −2 ) and dilute Cl − concentration (0.5 mmol L −1 ) for several hours (<50 h), which cannot meet the industrial requirements of practical electrolyzers.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal chalcogenides (TMCs) have gained significant attention as efficient catalysts due to their decent activity, particularly among the various non-noble metal catalysts. Recently, there has been considerable interest in exploring Ni- or Co-based metal sulfides as potential catalysts for the acidic HER, primarily because of their engineering versatility and cost-effectiveness. Earlier research has indicated that the electrochemical activity of CoSe 2 and NiSe 2 is attributed to the presence of chalcogenide atoms at their edges, similar to what has been observed in MoS 2 .…”
Section: Introductionmentioning
confidence: 99%